Strategi Personal Branding Sutiaji Dan Sofyan Edy Jarwoko Dalam Pilkada Kota Malang 2018 - Aminulloh, Akhirul; Ma’rifatun (Unitri Press, 2019)
Simultaneous elections in 2018 were held to elect new regional leaders including Malang City, which was followed by three candidate pairs. The pairs of candidates who advance in elections need the formation of a good image to be trusted by the people. But in its development towards the election there was the incident of the caught of two candidate pairs by the KPK, this certainly has a major impact on public trust in all candidate pairs. This study aims to know how the personal brand and personal branding of Sutiaji and Sofyan Edi Jarwoko as one of the candidates in the Malang Regional Election. This study uses descriptive qualitative methods. Data obtained through semi-structured interviews and documentation. The results of this study is the personal brand owned by Sutiaji is a religious person and Sofyan Edi Jarwoko is a nationalist. While the personal brand that is owned by the pair is formed from three elements, namely attributes in the form of SAE Jargon, personality as a populist leader, Value and benefits, namely vision, mission and work program are formed as a solution to the existing problems in Malang City. The personal branding stages of Sutiaji and Sofyan Edi Jarwoko are 4, namely determine theirself as a clean pairs, survey of people's opinions, position theirself as a populist leader, and managing the brand with an evaluation of the political communication activities carried out. Political communication is carried out to convey personal branding, there are three, namely through channels of mass communication, interpersonal communication channels, and organizational communication channels. Keywords : personal branding, political communications, Malang city election.